53 Exercise oxygen kinetic in hypertrophic cardiomyopathy: results from a multicentre cardiopulmonary exercise testing study. (8th December 2021) - Mapelli, Massimo; Romani, Simona; Magrì, Damiano; Merlo, Marco; Cittar, Marco; Masé, Marco; Muratori, Manuela; Gallo, Giovanna; Sclafani, Matteo; Carriere, Cosimo; Zaffalon, Denise; Salvioni, Elisabetta; et al.
Abstract: Aims: Reduced cardiac output (CO) has been considered crucial in symptoms' genesis in hypertrophic cardiomyopathy (HCM). We evaluated the cardiopulmonary exercise testing (CPET) response in HCM focusing on parameters strongly associated with stroke volume (SV) and cardiac output (CO), such as oxygen uptake (VO2 ) and O2 -pulse, considering both their absolute values and temporal behaviour during physical exercise. Methods and results: We enrolled 312 non-end stage HCM patients, divided according to left ventricle outflow tract obstruction (LVOTO) at rest or during Valsalva manoeuver (72% with LVOTO < 30; 10% between 30 and 49; and 18% ≥50 mmHg). Peak VO2 (percent of predicted), O2 -pulse, and ventilation to carbon dioxide production (VE/VCO2 ) slope did not change across LVOTO groups. Ninety-six (31%) HCM patients presented an abnormal O2 -pulse temporal behaviour, irrespective of LVOTO values. These patients showed lower peak systolic pressure, workload (106 ± 45 vs. 130 ± 49 W), VO2 (74 ± 17% vs. 80 ± 20%) and O2 -pulse (12 [9–14] vs. 14 [11–17]ml/beat), with higher VE/VCO2 slope (28 [25–31] vs. 27 [24–31]) ( P < 0.005 for all). Only two patients had an abnormal VO2 /work slope. Conclusions: None of CPET parameters, either as absolute values or dynamic relationships, were associated with LVOTO. Differently, an abnormal O2 -pulse exercise behaviour, which is strongly related to inadequate SV during exercise, correlates with reduced functional capacity (peak and anaerobic threshold VO2 and workload) and increased VE/VCO2 slope, helping identifying more advanced disease irrespectively of LVOTO. Adding O2 -pulse kinetics evaluation to standard CPET could lead to a potential incremental benefit in terms of HCM prognostic stratification and, then, therapeutic management.